THE USE OF ACOUSTIC TELEMETRY TO MONITOR FISH SPECIES IN MARINE PROTECTED AREAS: A SYSTEMATIC REVIEW WITH NOTES ON BRAZILIAN PERSPECTIVES: Uso da telemetria acústica no monitoramento de peixes em áreas marinhas protegidas: uma revisão sistemática com notas sobre as perspectivas brasileiras - Lippi, Daniel Lino; Menezes de Oliveira, Walter Dennis; Brasil Louro da Silveira, Camila; Padovani Ferreira, Beatrice (Arquivos de Ciências do Mar, 2021)
Inferring pathways used by organisms within ecosystems is essential to the design, management and evaluation of Marine Protected Areas (MPAs). This study aimed to present a systematic review on the literature regarding the use of acoustic telemetry to monitor marine fish movement and its application on MPAs. Searches were conducted on electronic databases. The first studies using telemetry on marine fish date back to the 60’s, while application on MPAs only appeared 30 years later. However, over the last decade, studies in MPAs accounted for 20% of the overall acoustic telemetry publications on marine fish species. Recent technological development has had an important impact on those results. The number of studies inside MPAs followed the number of general studies and coverage areas of MPAs declared around the world, although frequency of studies did not match MPA coverage in some countries. Developed countries scored more studies, probably due to the relative high cost of acoustic telemetry. Studies in Brazilian MPAs are scarce, with only one study available on elasmobranchs. Brazil has recently increased its MPA coverage to 26%, so it is expected to increase the need for MPA effectiveness studies. Brazilian participation on global tracking networks may help filling this gap. Keywords: PRISMA statement, fish movement, remote monitoring, MPA effectiveness, tracking networks